Enhancing field project management with agile-based digital tracking and reporting system - Manullang, Jontinus; Firdaus, Muhammad Huda; Sigalingging, Lasrida (Journal of Intelligent Decision Support System (IDSS), 2024)
This study introduces the Project On-site Tracker, a digital solution designed to enhance the efficiency and accuracy of recording and reporting project activities in the field. The research problem addressed the inefficiencies of traditional methods in construction project management, such as delayed data collection and manual reporting processes. The objective was to develop an integrated web and mobile application using Agile methodology, enabling real-time data recording, automatic report generation, and data analysis for informed decision-making. The system design utilized web technologies for backend operations and an Android framework for mobile accessibility, ensuring seamless data management across diverse project environments. Evaluation results demonstrated improved operational efficiency, faster decision-making capabilities, and enhanced transparency in project management processes. The implications suggest that adopting agile development methodologies in information systems can significantly improve responsiveness to user needs and project adaptability. This digital solution not only streamlines project management workflows but also lays groundwork for future enhancements in integrating advanced analytics and expanding compatibility with existing management systems.